Mediation as a “Negotiated Justice” - Stefanoaia, Mariana-Alina (Journal of Danubian Studies and Research, 2023)
Mediation is a structured process, in which a neutral and impartial third party, who has no decision-making power regarding the resulting solution, assists the parties in finding their own solutions to resolve the dispute. Mediation is based on the trust that the parties place in the mediator, as a person capable of facilitating negotiations between them and supporting them in resolving the conflict, by obtaining a mutually convenient, efficient and sustainable solution. The classical resolution of the conflict by referring it to the judicial authorities (police, prosecutor’s office, justice) often does not satisfy the interests of the parties, because it is a solution based on the winner-loser concept. Instead, resolving the conflict through mediation is the fruit of the meeting of the will of the parties. No one comes to impose their solution, therefore, the parties are the only ones in a position to decide. The role of the mediator is to facilitate the creation of a communication corridor between the parties, through which they can become aware of the best solution to the conflict between them. The mediation activity is performed equally for all persons, regardless of race, color, nationality, ethnic origin, language, religion, sex, opinion, political affiliation, wealth or social origin. The parties, individuals or legal entities, can resort to mediation without appealing to the judicial or arbitral bodies that will be relieved of numerous cases having as their object the settlement of misunderstandings between the parties. In conclusion, mediation, in a complex society and with different types of conflicts, represents the way outside the judicial system to the efficient, cheap and fast resolution of disputes.